Determinants of IBD‐related disability: a cross‐sectional survey from the GETAID. Issue 10 (5th April 2021) - Tannoury, Jenny; Nachury, Maria; Martins, Carole; Serrero, Melanie; Filippi, Jerome; Roblin, Xavier; Bourrier, Anne; Bouguen, Guillaume; Franchimont, Denis; Savoye, Guillaume; Buisson, Anthony; Louis, Edouard; et al.
Summary: Background: The burden of inflammatory bowel disease (IBD) is rising worldwide. The goal of IBD treatment is to achieve clinical and endoscopic remission but also prevent disability. Aims: To identify the predictive factors of disability in a large population of patients with IBD. Patients and methods: We conducted a cross‐sectional survey in 42 tertiary centres in France and Belgium. A self‐administered questionnaire was designed to explore patients and their IBD characteristics. IBD‐disk is a validated tool to measure disability in patients with IBD. The IBD‐disk score was then calculated for each patient. Based on a previous study, an overall IBD‐disk score ≥40 was associated with moderate‐to‐severe disability. Results: Among the 2011 patients, 1700 were analysed, including 746 (44%) in self‐reported clinical remission and 752 (44.2%) declaring clinical activity. The patient global assessment of global remission was missing in 200 (11.8%) of 1700 patients. Moderate‐to‐severe disability was significantly increased in patients with BMI >25 kg/m 2 (OR = 1.66; 95% CI [1.29‐2.14]), in those having perception of need for a psychotherapist (OR = 2.24; 95% CI [1.79‐3.05]) and social worker (OR = 1.54; 95% CI [1.08‐2.21]). Conversely, male gender (OR = 0.83; 95% CI [0.69‐0.99]), ulcerative colitis (OR = 0.69; 95% CI [0.53‐0.92]), self‐reported clinical remission (OR = 0.59; 95% CI [0.46‐0.77]) and employed or student occupational status (OR = 0.69; 95% CI [0.52‐0.92]) were inversely correlated with disability. Overall, 257 (34.5%) patients who declared being in clinical remission had disability. Conclusion: Determinants of IBD‐related disability include IBD‐related factors but also psychological and social factors. This highlights the importance of a multidisciplinary team in the management of patients with IBD. Abstract : The social and psychological impact of IBD may contribute to disability even in patients who declare to be in clinical remission.